2017
DOI: 10.1002/pssr.201700352
|View full text |Cite
|
Sign up to set email alerts
|

Surface State‐Induced Anomalous Negative Thermal Quenching of Multiferroic BiFeO3 Nanowires

Abstract: Wide‐bandgap semiconductor nanowires with surface defect emission centers have the potential to be used as sensitive thermometers and optical probes. Here, we show that the green luminescence of multiferroic BiFeO3 (BFO) nanowires shows an anomalous negative thermal quenching (NTQ) with increasing temperatures. The release of trapped carriers from localized surface defect states is suggested as the possible mechanism for the increased green luminescence which was experimentally observed at elevated temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
(70 reference statements)
3
11
0
Order By: Relevance
“…Yokogawa et al [56] observed a rise of the 2.65 eV blue band in ZnO at temperatures between 180 and 300 K with an activation energy of %0.1 eV and the quenching at higher temperatures with E A % 0.76 eV. Similar behavior of PL was observed for PL in Zn-doped CuAlS 2 , [57] Mg-doped GaN, [58] undoped ZnO, [59] ZnO nanostructures, [60] BiFeO 3 nanowires, [61] and other materials. Shibata [62] suggested that the negative thermal quenching is caused by thermal excitation of electrons from states lying below the initial state of PL transitions.…”
Section: Other Examples Of Negative Thermal Quenchingmentioning
confidence: 60%
“…Yokogawa et al [56] observed a rise of the 2.65 eV blue band in ZnO at temperatures between 180 and 300 K with an activation energy of %0.1 eV and the quenching at higher temperatures with E A % 0.76 eV. Similar behavior of PL was observed for PL in Zn-doped CuAlS 2 , [57] Mg-doped GaN, [58] undoped ZnO, [59] ZnO nanostructures, [60] BiFeO 3 nanowires, [61] and other materials. Shibata [62] suggested that the negative thermal quenching is caused by thermal excitation of electrons from states lying below the initial state of PL transitions.…”
Section: Other Examples Of Negative Thermal Quenchingmentioning
confidence: 60%
“…[20][21][22][23][24][25][26][27] Moreover, in our previously published work on multifferoic BFO nanowires (NWs) reasonable interpretation of the photoluminescence NTQ process in BFO NWs and detailed representation of the energy levels and E1, E2, E3, and E4 bands is given. 15 Briey, according to the multi-level model developed by Shibata 28 temperature dependent PL intensity can be expressed by activation energy for the process that increases the PL intensity with increasing temperature -NTQ ðE 0 q Þ and activation energy for the non-radiative channels ðE 00 j Þ. The activation energies of NTQ process ðE 0 q Þ in BFO nanowires were found to be a few times greater for E2 than for E1, E3, and E4.…”
Section: Temperature Dependant Bfo Emissionmentioning
confidence: 99%
“…Similar to BFO NWs, the lifetime is independent of the temperature change, resembling the static quenching behavior and can be explained in terms of multiple trapping and detrapping process. 15 Temperature sensing based on ratiometric method Since BFO NPs provide multiple emission peaks, a ratiometric approach to luminescence thermometry could be used. Such ratiometric measurements are insensitive to uctuations of excitation source light or other changes in measurement conditions and, therefore, act as self-referencing (i.e., measurements do not have to be referenced with any temperature standard).…”
Section: Temperature Dependent Luminescence Decay Lifetimementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, one-dimensional semiconductor nanowires (NWs) have been envisioned as a candidate for efficient and small devices [ 21 ]. The BFO NWs have recently been studied extensively in the quest to miniaturize devices, and these studies found that the BFO NWs have highly efficient carrier separation [ 19 ], negative thermal quenching of emission [ 22 ], extraordinary electrostatic response [ 23 ], and remarkably high polarization [ 24 ]. However, most of the research focuses on macroscopic properties and studies on the domain structure of single NW are still lacking.…”
Section: Introductionmentioning
confidence: 99%